2005
DOI: 10.1007/s10562-004-3760-y
|View full text |Cite
|
Sign up to set email alerts
|

CpMo(CO)3Cl as a precatalyst for the epoxidation of olefins

Abstract: The tricarbonyl complex CpMo(CO) 3 C1 was found to act as a precatalyst for the reaction of tert-butyl hydroperoxide and olefins to yield the corresponding epoxides and diols. Under the reaction conditions, oxidative decarbonylation leads to the formation of the dioxo complex CpMoO 2 Cl. The catalytic recyclability and the effect of temperature on the catalytic results have been examined, and a reaction mechanism proposed, supported by kinetic modelling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 18 publications
3
27
0
Order By: Relevance
“…It has been reported for (cyclopentadienyl)Mo(CO) 3 Cl-type compounds, used as catalyst precursors for cyclooctene epoxidation under similar reaction conditions, that the oxidative decarbonylation (OD) of the complexes with TBHP is necessary for the formation of active oxomolybdenum species. [16,17] A similar mechanistic feature may be involved for the compounds described above, as postulated in our recent work. [9] In general, no induction periods are observed for the carbonyl precursor complexes, suggesting that the OD is relatively fast and does not limit the rate of epoxidation of cyclooctene.…”
Section: Thesupporting
confidence: 66%
“…It has been reported for (cyclopentadienyl)Mo(CO) 3 Cl-type compounds, used as catalyst precursors for cyclooctene epoxidation under similar reaction conditions, that the oxidative decarbonylation (OD) of the complexes with TBHP is necessary for the formation of active oxomolybdenum species. [16,17] A similar mechanistic feature may be involved for the compounds described above, as postulated in our recent work. [9] In general, no induction periods are observed for the carbonyl precursor complexes, suggesting that the OD is relatively fast and does not limit the rate of epoxidation of cyclooctene.…”
Section: Thesupporting
confidence: 66%
“…complexes have been synthesized and applied in situ as precatalysts for epoxidation with hydroperoxide oxidants [20]. Subsequent kinetic and mechanistic work has shown that the dioxo complexes are further oxidized to oxo-peroxo species [CpMo(O)(g 2 -O 2 )R] with TBHP and the latter are also active catalysts in some cases [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…MoCp and Mo(L 2 )Br are isolobal [31] (Chart 1). It was a breakthrough to find out that these Mo(VI) complexes could be obtained in situ by addition of TBHP to the Mo(II) [CpMo(CO) 3 X] precursors [32,33] (Chart 1) and used directly. Kinetic experiments gave much insight on the mechanism, [34] which was extensively studied by DFT methods, by some of us, [12,13,35] and other groups.…”
Section: Methodsmentioning
confidence: 99%